Advocating the role of trained immunity in the pathogenesis of ME/CFS: a mini review - Humer, Bart; Dik, Willem A.; Versnel, Marjan A. (Frontiers in Immunology, 2025)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex chronic disease of which the underlying (molecular) mechanisms are mostly unknown. An estimated 0.89% of the global population is affected by ME/CFS. Most patients experience a multitude of symptoms that severely affect their lives. These symptoms include post-exertional malaise, chronic fatigue, sleep disorder, impaired cognitive functions, flu-like symptoms, and chronic immune activation. Therapy focusses on symptom management, as there are no drugs available. Approximately 60% of patients develop ME/CFS following an acute infection. Such a preceding infection may induce a state of trained immunity; defined as acquired, nonspecific, immunological memory of innate immune cells. Trained immune cells undergo long term epigenetic reprogramming, which leads to changes in chromatin accessibility, metabolism, and results in a hyperresponsive phenotype. Initially, trained immunity has only been demonstrated in peripheral blood monocytes and macrophages. However, more recent findings indicate that hematopoietic stem cells in the bone marrow are required for long-term persistence of trained immunity. While trained immunity is beneficial to combat infections, a disproportionate response may cause disease. We hypothesize that pronounced hyperresponsiveness of innate immune cells to stimuli could account for the aberrant activation of various immune pathways, thereby contributing to the pathophysiology of ME/CFS. In this mini review, we elaborate on the concept of trained immunity as a factor involved in the pathogenesis of ME/CFS by presenting evidence from other post-infectious diseases with symptoms that closely resemble those of ME/CFS.